Examining the Effect of Prototypical Leadership Style on Leader Effectiveness: Mediating role of Perceived Integrity and Moderating Role of Leader-leader Exchange - Elham Ebrahimi; SHabnam Zarjou (مدیریت دولتی)
Objective The main premise of social identity theory is that some leaders represent their group's identity and thus prescribe what followers should think, feel and do as members of the group. In this regard, prototypical leadership refers to a leadership style in which the leader is regarded as a representative of group identity of the followers and reflects the standards, values, and norms shared by the group members, and distinguishing them from other groups. The concept of prototypical leadership, at least in indigenous research, is an under-research topic. Therefore, the purpose of this article is to investigate this concept in the statistical population of the research in relation to other variables in the field of leadership, namely leader effectiveness, perceived integrity of the leader, and leader-leader exchange. Methods In this research, the effect of prototypical leadership on leadership effectiveness was examined. In the meantime, the mediating role of perceived leader's integrity and the moderating role of leader-leader exchange in the relationship between these two variables were measured. The study is considered an applied research in terms of its purpose, and is a descriptive survey in terms of data collection method. The study's statistical population consisted of employees working in teams at a telecommunications and information technology services company. In other words, in this company, organizational processes were carried out in the form of teams consisting of several members, a team leader and a team manager. Standard questionnaires were used to measure research variables. A statistical sample of 293 individuals was selected based on the tests used and G-Power software. Data were analyzed by structural equation modeling and partial least squares approach with Smart-PLS3 software.